h - Mori, Kensaku; Sakuma, Ichiro; Sato, Yoshinobu; Barillot, Christian; Navab, Nassir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The three-volume set LNCS 8149, 8150, and 8151 constitutes the refereed proceedings of the 16th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2013, held in Nagoya, Japan, in September 2013. Based on rigorous peer reviews, the program committee carefully selected 262 revised papers from 789 submissions for presentation in three volumes. The 81 papers included in the third volume have been organized in the following topical sections: image reconstruction and motion modeling; machine learning in medical image computing; imaging, reconstruction, and enhancement; segmentation; physiological modeling, simulation, and planning; intraoperative guidance and robotics; microscope, optical imaging, and histology; diffusion MRI; brain segmentation and atlases; and functional MRI and neuroscience applications.
Image reconstruction and motion modeling -- Machine learning in medical image computing -- Imaging, reconstruction, and enhancement -- Segmentation -- Physiological modeling, simulation, and planning -- Intraoperative guidance and robotics -- Microscope, optical imaging, and histology -- Diffusion MRI -- Brain segmentation and atlases -- Functional MRI and neuroscience applications.
Keywords: Computer science; Medical records -- Data processing; Radiology, Medical; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Artificial Intelligence (incl. Robotics).; Imaging / Radiology; Health Informatics